EVALUASI PSIKOEDUKASI TERHADAP PENINGKATAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK: KAJIAN LITERATUR - Muhamad Jauhar; widya Agustiani; Sugih Wijayati (Viva Medika, 2020)
Chronic kidney disease is one of the health problems in the world. Chronic kidney disease as a complication of other chronic diseases such as hypertension. Management of chronic kidney disease in the final stages is done through hemodialysis therapy. The therapy is carried out throughout the patient's life. One impact that occurs if the problem is not handled properly is a decrease in quality of life. One non-pharmacological intervention to improve the quality of life is psychoeducation. The design of this study used a literature review from the journal database PubMed and Google Scholar obtained 10 research articles. Keywords used are psychoeducation and, Chronic Kidney Disease","quality of life and, Chronic Kidney Disease. Analysis of the research article uses a table format containing the title, author, year, method, results, and recommendations. Inclusion criteria for the last 5 years of publication deadline and original research. Based on the results of the analysis found that psychoeducation therapy can improve the quality of life of patients with chronic kidney disease. The advantage is that it can increase self-acceptance of health problems experienced. The disadvantage is the therapeutic effect shows differences in each patient because it is influenced by several factors. The results of the analysis can be used as a baseline for nurses in developing non-pharmacological interventions in the process of nursing care for clients with chronic kidney disease with problems of decreased quality of life. So that the psychological impact and complications of the disease can be prevented.